TEACHERS' INNOVATIONS IN DEVELOPING ISLAMIC RELIGIOUS EDUCATION TEACHING MATERIALS THROUGH INTERACTIVE DIGITAL MEDIA IN JUNIOR HIGH SCHOOLS - Nuria Sundari; Neni (Academic Bright Collaboration, 2026)
This study aims to describe teachers’ innovations in developing Islamic Religious Education teaching materials through interactive digital media at SMP Negeri 16 Tebo Regency, identify the supporting and inhibiting factors in its implementation, and describe the perceived impact on the Islamic Religious Education learning process. This study employs a qualitative approach with a descriptive research design. The study was conducted at SMP Negeri 16 in Tebo Regency, involving one Islamic Religious Education teacher and five ninth-grade students as informants. Data were collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and concluding, while data validity was strengthened through triangulation of sources and techniques. The results indicate that the teacher implemented instructional innovations by utilizing interactive digital media based on Canva, presented in the form of PowerPoint presentations that integrated text, images, animations, audio, and interactive visual elements. Supporting factors for these innovations included the teacher’s technological proficiency, school support, and student enthusiasm. Meanwhile, inhibiting factors include limited facilities and infrastructure, unstable internet access, and limited learning devices. The findings also indicate that teachers and students view the use of interactive digital media as helping to increase student interest in learning, encouraging more active participation, and facilitating the understanding of Islamic Religious Education material. This study indicates that interactive digital media can serve as an alternative instructional strategy to support the Islamic Religious Education learning process. However, since the study was conducted at a single school with a limited number of informants, the results are not intended to be generalized to a broader context. The originality of this study lies in its examination of teachers’ innovations in developing Islamic Religious Education teaching materials using Canva at a school with limited technological facilities. This study provides an empirical contribution regarding the practice of utilizing interactive digital media in Islamic Religious Education at the junior high school level.